Zn‐Doped P‐Type InAs Nanocrystal Quantum Dots. Issue 5 (16th December 2022) - Asor, Lior; Liu, Jing; Xiang, Shuting; Tessler, Nir; Frenkel, Anatoly I.; Banin, Uri
Abstract: Doped heavy metal‐free III–V semiconductor nanocrystal quantum dots (QDs) are of great interest both from the fundamental aspects of doping in highly confined structures, and from the applicative side of utilizing such building blocks in the fabrication of p–n homojunction devices. InAs nanocrystals (NCs), that are of particular relevance for short‐wave IR detection and emission applications, manifest heavy n‐type character poising a challenge for their transition to p‐type behavior. The p‐type doping of InAs NCs is presented with Zn – enabling control over the charge carrier type in InAs QDs field effect transistors. The post‐synthesis doping reaction mechanism is studied for Zn precursors with varying reactivity. Successful p‐type doping is achieved by the more reactive precursor, diethylzinc. Substitutional doping by Zn 2+ replacing In 3+ is established by X‐ray absorption spectroscopy analysis. Furthermore, enhanced near infrared photoluminescence is observed due to surface passivation by Zn as indicated from elemental mapping utilizing high‐resolution electron microscopy corroborated by X‐ray photoelectron spectroscopy study. The demonstrated ability to control the carrier type, along with the improved emission characteristics, paves the way towards fabrication of optoelectronic devices active in the short‐wave infrared region utilizing heavy‐metal free nanocrystal building blocks. Abstract : Post‐synthesis doping of InAs nanocrystals with Zn enables the fabrication of heavy metal free, RoHS compliant nanocrystal‐based field effect transistors, which exhibit either n‐ or p‐type characteristics. Advanced structural characterization of the doped nanocrystals highlights the importance of Zn dopant chemistry on the doping efficiency. This study sets the stage for future development of nanocrystals‐based opto‐electronics applications.